Close contact - Foster, Lori, 1958- (Foster, Lori, 1958- Body Armor novel., 2017)
MMA fighter Miles Dartman's casual arrangement with personal shopper Maxi Nevar would be many men's fantasy. She seeks him out, they have mindblowing sex, she leaves. Rinse, repeat. Yet lately, Miles wants more. And when Maxi requests his services via the Body Armor security agency, he's ready to finally break through her defenses<U+2014>and protect her day and night. Receiving a large inheritance has brought chaos and uncertainty into Maxi's life. Her ex has resurfaced, along with lots of former "friends," and someone is making mysterious threats. Then there's Miles, who doesn't ask for anything<U+2026>except her trust. Pleasure is easy. Now Maxi has to give her heart as well as her body<U+2026>or risk losing a man who could be everything she needs.